A Comparative Study of Unsaturated Resin/Graphite Microchip and Nano-Graphite Microchip Composites Prepared by Electric Field. Issue 206 (23rd March 2020) - Zhang, Hongyan; Wang, Haiquan
Abstract: Graphite microsheets as conductive fillers have their unique advantages compared with a traditional conductive fillers such as carbon black. Graphite microsheets have a large diameter-thickness ratio, which greatly reduces the percolation threshold of conductive composite system with graphite microsheets as conductive fillers. Under the action of applied electric field, the orientation of graphite microsheets in polymers changes the distribution of graphite in polymers. The conductivity of the composites can be changed. Because of the large diameter-thickness ratio, the nanographite microchip is easier to form conductive pathways in the composites. It can be imagined that the conductivity of ordinary graphite nanosheets can be achieved at a lower content as the ultra-fine dispersed graphite nanosheets. With the use of the conductive materials stated above and through the effect of applied electric field, we were able to get a new method of processing materials and functional materials with a higher design and better comprehensive performance. As conductive fillers, graphite nanosheets can be induced by the AC electric field in unsaturated polyester resin and then prepared oriented unsaturated polyester resin/graphite nanosheets composite. Compared with one-dimensional structure of carbon nanofiber and carbon nanotubes, two-dimensional lake-like shape graphite nanosheets have high aspect ratio. Applying an electric field during the preparation of the composite, graphite nanosheets can be oriented conquering the shearing action of viscous in an insulating polymer matrix due to the cooperative effect of the electric torque exerted by the electric field directly on the nanosheets. Finally, through the change of electric current of composite materials prepared in different media under electric field, we determine the influence factors of conductivity of composite materials and the conductive mechanism of nano-graphite micro-sheets under electric field.